2010
DOI: 10.1007/s10096-010-0929-8
|View full text |Cite
|
Sign up to set email alerts
|

Changing etiology of community-acquired bacterial meningitis in adults: a nationwide multicenter study in Korea

Abstract: Epidemiologic data on the etiologic organisms is important for appropriate empirical antibiotic treatment of bacterial meningitis. We identified the etiologies of community-acquired bacterial meningitis in Korean adults and the associated epidemiological factors. A retrospective, multicenter nationwide study was carried out. Patients 18 years of age or older with community-acquired bacterial meningitis with a confirmed pathogen were enrolled. Demographic, clinical, and microbiological data were collected. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…It was also found that large-area cerebral infarction occurs in mice in which the NT-4/5 receptor gene was knocked out, indicating that NT-4/5 can reduce the cerebral susceptibility to ischemic injury. In addition, NT-4/5 can promote the survival, growth, and differentiation of neurons, and protect the hippocampus and cortical neurons from excitatory toxins and metabolic injury (Moon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that large-area cerebral infarction occurs in mice in which the NT-4/5 receptor gene was knocked out, indicating that NT-4/5 can reduce the cerebral susceptibility to ischemic injury. In addition, NT-4/5 can promote the survival, growth, and differentiation of neurons, and protect the hippocampus and cortical neurons from excitatory toxins and metabolic injury (Moon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae has been the most common etiology of community-acquired, bacterial meningitis in adults in most countries [1][2][3][4], and high rates of mortality and neurological sequelae in pneumococcal meningitis have been problematic despite antibiotic therapy and advanced critical care [1][2][3][4][5]. Severe inflammatory response in the subarachnoid space of the patients with bacterial meningitis receiving antibiotic treatment has been known to be associated with mortality and neurological sequelae [6].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic trends between western and eastern countries appear to differ in the percentage contributions of the major species inducing bacterial and fungal meningitis. In surveys from western countries, Escherichia coli was the leading pathogen among aerobic Gram-negative bacilli, which account for 4.3-12.3% of the pathogens causing bacterial meningitis [6]. In Asia, Klebsiella pneumoniae was the most common among the implicated Gram-negative pathogens and the overall incidence of meningitis caused by Gram-negative bacilli is 7.6-28.8% [6,7], which is about twice the incidence in western countries.…”
Section: Introductionmentioning
confidence: 99%